Modern tradition and identity. Architecture in Uruguay during the second half of the 20th century - Frontini, Pablo (Universidad ORT Uruguay, 2018)
Latin America is the region in which, for the first time in the history of Western architecture, a normative system for the organization of the physical environment —of maximum transcendence such as the modern one— has had a second development opportunity, once its trajectory was ended in its place of origin.This observation leads us to try to understand the process of transcultural synthesis that occurs through the adaptation of certain philosophical, organizational and aesthetic bases to a reality substantially different from the one in which they were conceived.Within some general circumstances that are summarized in this text, certain constants can be observed. These principles guided the production of modern architecture in Uruguay during the second half of the 20th century. Avoiding the pretension of making a closed or definitive clasification, it seems pertinent to try to define and systematize those values that can be found as constant —although in their most diverse expressions—, both in architectural practice and in theoretical explanations of those who have defined the profile of the best urban areas of the country